Synthesis of zinc oxide nanostructures and their applications as field electron emission cathodes and photocatalysts / Hartini Ahmad Rafaie - Hartini, Ahmad Rafaie (2016)
Pure and Fe, Al or Mg doped zinc oxide nanostructures were synthesized by the sol-gel method using conventional (HMTA) or biomaterial (Citrus aurantifolia(CA)) reagent as the reducing agents. The effect of substrate (Al, glass, stainless steel) using HMTA was studied. It was discovered that glass was the most efficient substrate, while stainless steel was the least efficient in terms of ZnO nanorods growth rate. This was due to the reactivity of the metallic substrates with the chemicals used during synthesis. The effect of deposition time from 0.5 hour to 4 hours showed improved crystallinity, uniformity and increase in diameter with deposition time. Doping with Fe and Al at different concentrations was verified by shifts in the XRD peak of the zinc oxide (001) diffraction plane towards smaller or higher angle and EDX analysis. Using CA as the reducing agent, growth rate was significantly affected by the solution pH. ZnO nanorods prepared at different pH values using CA. Enhanced ZnO formation was observed in neutral and alkaline compared to acidic solution. This was due to the abundance of OH- ions in non acidic solutions which promoted the formation of the Zn(OH)2 intermediate species. A direct correlation between doping level and the concentration of Mg used was observed. XRD peak shiftstoward higher angleagain indicated dopingwhich was further verified using EDX. FEE properties of pure ZnO synthesized at between 0.5 and 4 hours showed marked differences due to the geometrical affect. Increase in ZnO nanorods aspect ratio for sample synthesized at longer time yielded higher field enhancement factor values while reducing the turn-on and threshold electric field values. ZnO doped with different level of Alsynthesized at constant deposition time, gave similar field enhancement values due to the similar geometrical structure of the samples. The effect of Al doping was observed in the form of reducing the turn-on and threshold electric field values. Similar effects were observed for Mg-doped ZnO iii samples. On the effect of AgNPs decoration on the efficiency of ZnO as photocatalysts revealed that microsized ZnO particles decorated with nanosized Ag were significantly more efficient than nanosized ZnO particles decorated with nanosized Ag. This phenomena was explain in terms of the light shield effect in the nanosized samples based on commonly accepted photocatalytic degradation of dye.